Virgilio y sus comentarios renacentistas (I) - Jiménez Calvente, Teresa (Estudios Clásicos, 2001)
The authoress explains how Renaissance scholars studied Virgil works in a different way from Middle Age tradition. She focuses on Juan Luis de la Cerda, a quite unknown Spanish jesuit priest who wrote a very detailed interesting commentary on Aeneid. De la Cerda tries to penetrate into poet's mind, mens poetae, as a methodological way of approaching to his work. Different methods for commentary are examined, not only by De la Cerda but by Calderini, Poliziano, Beroald and many others. Servius, the ancient scholiast, is always present; he influences most of the commentators.